Association between Iron Deficiency Anemia with Helicobacter Pylori Infection - Farah Bashir, Hefsa Qamar, Sahil Sardana, Syed Ali Raza, Meena Bai, Fayaz Ahmed Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to examine the link between helicobacter pylori infection and iron deficiency anaemia (IDA). Study Design: Retrospective study Place and Duration: Poonch Medical College Rawalakot and Dr. Ziauddin Hospital, North Nazim Abad, Karachi, during from July, 2021 to Dec, 2021. Methods: Eighty-six patients aged 18-55 were presented. All patients gave written informed permission that included age, sex, BMI, education, and citizenship. All study participants had helicobacter pylori. Participants' blood samples were tested for serum iron, transferrin saturation, ferritin, and total iron-binding capacity. A urea breath test, stool antigen testing, a fast urease test, or histopathology was used to detect H. pylori. Data was analyzed using SPSS 19.0. Results: Majority of the patients 43 (50%) were aged between 31-40, followed by 25 (29.1%) patients of age 18-30 years and 18 (20.9%) were aged 41-55 years. Among 86 cases, 55 (63.9%) had body mass index <25kg/m2 and 31 (36.1%) had body mass index >25kg/m2. Frequency of males was higher 50 (58.1%) as compared to females 36 (41.9%). Stomach pain, nausea, loss of appetite, frequent burping and bloating was the most common symptoms among all cases. The frequency of IDA was found in 38 (44.2%) in which majority of the patients were aged between 35-5 years and females were higher in number among them. Conclusion: In this study, we found that the prevalence of iron deficiency anemia was considerably greater among patients with helicobacter pylori infection, and that the majority of adult patients were females. Keywords: Symptoms, Iron Deficiency Anemia (IDA), Adult Patients, H.pylori infection, Association